2022
DOI: 10.1186/s12877-022-03191-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinical features and mortality in very old unvaccinated patients (≥ 80 years) hospitalized with COVID-19 during the first and successive waves from the multicenter SEMI-COVID-19 Registry (Spain)

Abstract: Background Old age is one of the most important risk factors for severe COVID-19. Few studies have analyzed changes in the clinical characteristics and prognosis of COVID-19 among older adults before the availability of vaccines. This work analyzes differences in clinical features and mortality in unvaccinated very old adults during the first and successive COVID-19 waves in Spain. Methods This nationwide, multicenter, retrospective cohort study an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
1
9
1
Order By: Relevance
“…as the most common symptoms in cohorts of elderly Spanish patients hospitalized for COVID-19. [23][24][25] Consistent with the ndings of other studies, the elderly individuals in our cohort predominantly presented elevated in ammatory markers, such as ferritin and CRP, and frequent elevation of D-dimer and LDH. 23,24 This laboratory pro le did not differ across the various epidemic waves.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…as the most common symptoms in cohorts of elderly Spanish patients hospitalized for COVID-19. [23][24][25] Consistent with the ndings of other studies, the elderly individuals in our cohort predominantly presented elevated in ammatory markers, such as ferritin and CRP, and frequent elevation of D-dimer and LDH. 23,24 This laboratory pro le did not differ across the various epidemic waves.…”
Section: Discussionsupporting
confidence: 91%
“…Other cohort studies assessing hospitalized elderly patients have reported acute kidney injury, which is likely related to tubular injury caused by local and systemic in ammation and immune systems, aggravated by hemodynamic instability. 23,24,30 Moreover, underlying chronic kidney disease is frequent among octogenarians, further contributing to an increased risk of developing acute kidney injury during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 243 outpatients with COVID-19, sulodexide, an oral mixture of glycosaminoglycans (low-molecular-weight heparin and dermatan sulfate), decreased the need for hospitalization. 23 Although thromboinflammation was suggested as a final common pathway for clinical deterioration early in the pandemic, 24 , 25 subsequent data support non–thrombosis-based cardiovascular diseases 26 , 27 such as heart failure and sepsis as greater contributors to morbidity and mortality. 4 , 28 A reduction in thrombosis, clinical deterioration, and death in patients with COVID-19 has also been explained by more widespread implementation of corticosteroids, monoclonal antibodies, and antiviral agents, as well as nearly 70% of the population being fully vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Ramos-Rincon JM et al 17 studied older population in Spain. The study included 4545 cases during the first wave, and 1408 cases in the successive waves.…”
Section: Discussionmentioning
confidence: 99%